Three-point functions in superstring theory on AdS3 x S3 x T4 - Cardona Giraldo, Carlos Andres (2009)
We consider R and NS spectral flow sectors of type IIB superstring theory on AdS3× S3×T4 in the   context of the AdS3/CFT2 correspondence. We present a derivation of the vertex operators  creating  spectral flow images of chiral primary states previously proposed in the literature. We  compute spectral flow conserving three-point functions involving these operators on the sphere.  Using  the bulk-to-boundary dictionary, we compare the results with the corresponding correlators in  the dual conformal field theory, the symmetric product orbifold of T4. In the limit of small string  coupling, agreement is found in all the cases considered.